Woody Species Composition Analysis of Shawo Sacred Forest, Ethiopia - Agidew, Samuel Tizazu; Mezgebe, Alemayehu Hailemicael (International Journal of Applied Sciences and Biotechnology, 2019)
In sacred forests of indigenous communities, landscapes are deemed sacred and are protected through social norms and spiritual values. The main objective of this study was to analyze the woody species composition of Shawo forest and explore the traditional governing systems that safeguard the sacred forest up to the present. Systematic sampling method was used to collect data. Accordingly, 42 quadrats each with 400 m2 (20 m X 20 m) was laid along the 14 transect lines. All woody plant species were collected and identified in each of these quadrats. Vegetation parameters such as DBH an Height of each quadrat were recorded. Interview and group discussion were held with local community to gather socio-cultural information. From the result, 16 plant species were found. The average plant density was 499 individual ha-1 with DBH and H value of 9.21 cm and 10.43 m respecitively.. The maximum mean plant height was 39.43 m (Syzygium guineense).The total basal area of all plant species was found to be 56.1 m2.ha-1. From the total plant species of Shawo forest Syzygium guineense has the largest basal area 35.77 m2.ha-1 (63.77%) occurring in all 42 plots. The most important plant species of Shawo forest was Syzygium guineense with important value index (IVI) of 151.7 contributing to 50.57% of total IVI. For future sustainability of Shawo forest, community traditional conservation practices should be appreciated and supported.